Anti-Saccharomyces cerevisiae antibodies in twins with inflammatory bowel disease. Issue 9 (29th April 2005) - Halfvarson, J; Standaert-Vitse, A; Järnerot, G; Sendid, B; Jouault, T; Bodin, L; Duhamel, A; Colombel, J F; Tysk, C; Poulain, D
Abstract : Background and aims: An increased occurrence of anti- Saccharomyces cerevisiae antibodies (ASCA) is reported in unaffected members of families with Crohn's disease. Whether ASCA is a familial trait due to genetic factors or is caused by exposure to environmental factors is unknown. To assess the genetic influence of ASCA we studied its occurrence in a twin population. Patients and methods: ASCA were analysed in 98 twin pairs with inflammatory bowel disease and were related to clinical phenotype and CARD15/NOD2 genotype. Results: ASCA were more common in Crohn's disease than in ulcerative colitis (40/70 (57%) twins v 5/43 (12%) twins). Associations with ileal Crohn's disease, stricturing/penetrating behaviour, and young age, but not CARD15/NOD2 were confirmed. ASCA were found in 1/20 (5%) healthy siblings in discordant monozygotic pairs with Crohn's disease compared with 7/27 (26%) in discordant dizygotic pairs. Using the intraclass correlation coefficient (ICC), no agreement in ASCA titres was observed in discordant twin pairs with Crohn's disease, in monozygotic (ICC = −0.02) or dizygotic (ICC = −0.26) pairs. In contrast, strong agreement was seen within concordant monozygotic twin pairs with Crohn's disease (ICC = 0.76). Conclusions: These findings question the concept of ASCA as a marker of genetic susceptibility for Crohn's disease. The agreement in ASCA titres within concordant monozygotic twin pairs with Crohn's disease, suggests that the level of increase is genetically determined. We propose that ASCA are a marker of a response to an environmental antigen and that a specific gene(s) other than CARD15/NOD2 determines the level of response and perhaps also specific phenotypic characteristics.